Design and Analysis Quarter Car Test Rig Model by Using Simulation Software - Mohamad Izzauddin Ahmad,; Syabillah Sulaiman,; Muhammad Asri Azizul, (Progress in Engineering Application and Technology, 2024)
This thesis presents the design and analysis of a quarter car test rig model aimed at studying fundamental vehicle dynamics. The objective of this research is to develop a new quarter car test rig model and the safety of the structure has been analyzed by using Solidwork software. To achieve this, study of previous quarter car test rig models is conducted through literature review to find a base model. After that, new variants of designs have been formed through design tree and all designs based on the base model. From all variants of design, the best design of the variants has been selected through screening process and lastly, a scoring concept method has been used to find the final design. The parameters considered for comparison include the structure, materials, cost, dimension and the most important criteria is Finite Element Analysis (FEA) simulation result of the test rigs. The anticipated outcomes of the analysis include evaluating the maximum stress, displacement, and other relevant outputs, which will determine the suitability of the test rig for real-world applications. The results obtained from this study will provide valuable insights into the mechanical performance of the quarter car test rig model, helping to ensure its safety and effectiveness. This research contributes to the field of vehicle dynamics by providing a comprehensive understanding of the design and analysis process for quarter car test rig models.